Factors associated with the adoption of a digital health service by patent proprietary medicine vendors (PPMVs) in Lagos, Nigeria. (December 2022) - Agha, Sohail; Ruiz-Gaona, Laura Alejandra; Friedman, Jed; Cheikh, Nejma; Gorgens, Marelize
Background: Patent proprietary medicine vendors (PPMVs) are the first point of care for low-income Nigerian households. They are likely to have an important role in a digital care pathway established for low-income Nigerian women and children. Yet, little is known about what drives the adoption of digital platforms by PPMVs. Methods: This study explores factors associated with the adoption of a digital service, NaijaCare, created to enable PPMVs to increase the range and quality of products and services they offer. A structured, quantitative, face-to-face survey was conducted among 248 PPMVs in Lagos in February and March 2020. Multivariate analysis was conducted to identify factors associated with the adoption of NaijaCare. Results: Women comprise the majority (67%) of medicine vendors in Lagos. Most medicine vendors (64%) had gotten health training on the job. About a quarter (27%) of medicine vendors reported seeking business advice on the internet. Medicine vendors who had obtained on-the-job training had a 12.31 times higher odds ratio ( p < 0.01) of adopting the digital service. Medicine vendors who sought business advice on the internet had a 6.48 times higher odds ratio ( p < 0.001) of adopting NaijaCare. Conclusion: The study findings suggest that PPMVs' use of the digital service was driven by their desire to increase business profits. Digital care pathways targeting low-income households should be aligned with the business interests of informal providers.